Ultra-deep profiling of alternatively spliced Drosophila Dscam isoforms by circularization-assisted multi-segment sequencing - Sun, Wei; You, Xintian; Gogol-Döring, Andreas; He, Haihuai; Kise, Yoshiaki; Sohn, Madlen; Chen, Tao; Klebes, Ansgar; Schmucker, Dietmar; Chen, Wei (The EMBO journal, 2013)
The Drosophila melanogaster gene Dscam ( Down syndrome cell adhesion molecule ) can generate thousands of different ectodomains via mutual exclusive splicing of three large exon clusters. The isoform diversity plays a profound role in both neuronal wiring and pathogen recognition. However, the isoform expression pattern at the global level remained unexplored. Here, we developed a novel method that allows for direct quantification of the alternatively spliced exon combinations from over hundreds of millions of Dscam transcripts in one sequencing run. With unprecedented sequencing depth, we detected a total of 18 496 isoforms, out of 19 008 theoretically possible combinations. Importantly, we demonstrated that alternative splicing between different clusters is independent. Moreover, the isoforms were expressed across a broad dynamic range, with significant bias in cell/tissue and developmental stage‐specific patterns. Hitherto underappreciated, such bias can dramatically reduce the ability of neurons to display unique surface receptor codes. Therefore, the seemingly excessive diversity encoded in the Dscam locus might nevertheless be essential for a robust self and non‐self discrimination in neurons. Alternative splicing of the Down syndrome cell adhesion molecule, Dscam, can generate thousands of different isoforms. A novel method is developed that quantitatively profiles Dscam isoform expression revealing dynamic and differential splicing patterns during development.